1989
DOI: 10.1159/000181283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Growth Hormone on Urinary <sup>15</sup>N-Nitrogen Balance in Girls with Turner Syndrome as Compared to Children with Growth Hormone Deficiency

Abstract: 15N-nitrogen balances before and on human growth hormone (hGH) were studied in 13 girls with Turner syndrome (TS) aged 4.4–16 (median 13.2) years (45, X0 or equivalent, no X0/XX mosaicism, no estrogen replacement). The results were compared with those reported from 9 patients with growth hormone deficiency (GHD). The TS patients received subcutaneous hGH doses of 2 × 3 (group A, n = 6), 3 × 2 (group B, n = 3), or 2 × 6 (group C, n = 4) IU/m2 on consecutive days. The mean 15N do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…growth hormone, IGF-I). At present, data supporting the likelihood of success with the former maneuver are limited (3 1,32); the latter strategy, although effective in animals (33), older children (34), and adults (35), has not been evaluated in LBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…growth hormone, IGF-I). At present, data supporting the likelihood of success with the former maneuver are limited (3 1,32); the latter strategy, although effective in animals (33), older children (34), and adults (35), has not been evaluated in LBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…0,15 IU/kg per day) are required to accelerate height velocity [16,17,25,29]. Similarly, metabolic studies on the effect of hGH on urinary 15N-nitrogen balance also showed that TS patients require twice the dose of hGH to obtain an effect similar to that observed in patients with GH deficiency [19].…”
Section: Resultsmentioning
confidence: 84%
“…the balance became considerably more posi tive in the GH-dcficicnt patients [45], while in subjects with normal GH secretion, such as girls with Turner syn drome. it remained almost unchanged [46], When normal subjects were given testosterone, there was a marked l5N retention, which was in the same order of magnitude as that induced by hGH in the GH-deficient patients.…”
Section: Synergistic Metabolic Effectsmentioning
confidence: 72%